1974
DOI: 10.1002/jsfa.2740250306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by carboxylic acids of an o‐diphenol oxidase from Prunus avium fruits

Abstract: Aromatic carboxylic acids strongly inhibited 4-methylcatechol oxidation by an o-diphenol oxidase extracted from sweet cherry fruits (Prunus uvium). Esterification of the acids decreased their inhibitory strength. Inhibitors containing the benzene nucleus showed a greater effectiveness than the corresponding aliphatic and heterocyclic compounds (except 2-naphthalenecarboxylic acid). Similar inhibitory effects were observed by replacing the benzene ring with a highly unsaturated open chain. The inhibitory proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2

Year Published

1975
1975
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 8 publications
1
47
2
Order By: Relevance
“…Results for the Ki values have been summarized in Table 1. It is proposed that the catalytic and inhibitory sites of the enzyme seem to be close together [10]. The uncompetitive type of inhibition for propanoic acid indicates that it should be bind at a site distinct from the active site and bind just with the enzyme-substrate (ES) complex and not with the free enzyme (E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results for the Ki values have been summarized in Table 1. It is proposed that the catalytic and inhibitory sites of the enzyme seem to be close together [10]. The uncompetitive type of inhibition for propanoic acid indicates that it should be bind at a site distinct from the active site and bind just with the enzyme-substrate (ES) complex and not with the free enzyme (E).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of acid derivatives, the mechanism of inhibition involves the formation of copper-carboxylic acid complex at binuclear copper site of the enzyme [10,39]. P-coumaric acid and its corresponding dihydroxy derivative, caffeic acid bind to the free copper through their carboxylic terminal that is attached to a sp 2 carbon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hydroxyl groups on aromatic ring (ring B) of myricetin might play an important role in high banana PPO inhibitory activity. Some researchers also indicated that p-coumaric acid was effective in enzymatic browning inhibition in potato (Macrae & Duggleby, 1968) and apple (Pifferi, Baldassari, & Cultrera, 1974;Walker & Wilson, 1975). Moreover, inhibitory effects of p-coumaric acid on grape PPO (Gunata, Sapis, & Moutounet, 1987) and mushroom tyrosinase (MellayHamon & Criton, 2009) were also higher than t-cinnamic acid.…”
Section: Pse and Its Ultrafiltered Fractions On Banana Ppo Activitymentioning
confidence: 99%
“…Some authors have evaluated the influence of the structure of the phenolic compounds on the capacity to modify PPO activity (Kuttner and Wagreich 1953;Soler-Martinez e f a1 1965;Pifferi et al 1974;Mayer and Harel 1979;Sato 1979). Kuttner and Wagreich (1953) investigating the effects of different benzoic acids and related compounds on mushroom PPO, reported their finding that benzoic acid was the best inhibitor and that the inhibitory strength decreased with esterification or ionisation of the benzoic carboxylic group.…”
Section: Introductionmentioning
confidence: 99%